2020
DOI: 10.1002/jdd.12038
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of an instrument to assess critical thinking disposition and metacognition in dental students

Abstract: Objective The purpose of this study was to determine the psychometric properties of instruments designed to assess the critical thinking domains of disposition and metacognition in a dental student population. Methods Two instruments originally developed to assess disposition and metacognition domains in undergraduate student populations were administered to dental students from 3 classes in the Spring of 2019. The overall response rate was 73%. Sampling adequacy was established for both domains. Exploratory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
(21 reference statements)
0
5
0
2
Order By: Relevance
“…Disposition relates to a person's inclination to learn critical thinking skills, and unlike for skills that can be assessed at the beginning of the program and reassessed at the end of each module to understand the changes, 5 for disposition, time may be needed for changes to be found, and the changes may be relatively smaller 17,18 . Currently, however, there is no consensus on how critical thinking should be measured, 19,20 or on the ideal measuring instrument for use in dental education 17,21–24 . A previous systemic review identified the California Critical Thinking Disposition Inventory (CCTDI) as an instrument that is used to measure critical thinking disposition 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disposition relates to a person's inclination to learn critical thinking skills, and unlike for skills that can be assessed at the beginning of the program and reassessed at the end of each module to understand the changes, 5 for disposition, time may be needed for changes to be found, and the changes may be relatively smaller 17,18 . Currently, however, there is no consensus on how critical thinking should be measured, 19,20 or on the ideal measuring instrument for use in dental education 17,21–24 . A previous systemic review identified the California Critical Thinking Disposition Inventory (CCTDI) as an instrument that is used to measure critical thinking disposition 22 .…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Currently, however, there is no consensus on how critical thinking should be measured, 19,20 or on the ideal measuring instrument for use in dental education. 17,[21][22][23][24] A previous systemic review identified the California Critical Thinking Disposition Inventory (CCTDI) as an instrument that is used to measure critical thinking disposition. 22 Although this review found a problem with the psychometric evidence of the instrument, 22 the CCTDI was reported to have good reliability [25][26][27] ; to have correlations with other assessments such as knowledge, faculty ratings, and clinical reasoning for dental hygiene students 28 ; and to have a potential relationship with clinical advisor rankings in dental students.…”
Section: Introductionmentioning
confidence: 99%
“…18 Consequently, we adapted an instrument that had never been used in dental education and established validity and reliability to support its use. 19 The approach was to focus on the disposition and metacognition aspects of critical thinking, which may be the most important facets of critical thinking development. 20 Disposition has been defined as a motivation to act in habitual but potentially malleable ways.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, las intervenciones no produjeron ninguna interacción significativa en la regulación de cognición, puntajes de exámenes o notas finales. Concluyeron que se recomiendan más estudios sobre metacognición en el área de la educación de fisiología y examinar la forma en que los datos De igual manera, el pensamiento crítico se puede relacionar con la metacognición, como lo analizaron Anders et al (2020), quienes determinaron las propiedades psicométricas de los instrumentos diseñados para evaluar los dominios de pensamiento crítico y metacognición en estudiantes de odontología. Concluyeron que ambos instrumentos tienen suficiente validez y confiabilidad para aplicarlos posteriormente en otras investigaciones.…”
Section: Antecedentes Internacionales De La Categoria Herramientaunclassified
“…La competencia del pensamiento crítico se hace esencial en la educación dental e incluye diversas habilidades, como la interpretación, análisis, inferencia, evaluación y explicación (Anders et al, 2020).…”
Section: Tablaunclassified